What to do about Climate Change-Caused Flooding and the Associated Diseases in Rivers State of Nigeria (Global Journal of Human-Social Science, 2015)
The prime focus of the study is to explain what to do about climate change-caused flooding and the associated diseases in Rivers State of Nigeria. In doing so, this work gives an overview of climate change-caused flooding and effects of flooding on people in flooded areas, as well as explains flooding associated diseases in Rivers State. Besides this, it further proffers legislative, short-term and long-term measures that will help reduce if not eliminate flooding and its associated diseases in Rivers State of today, and indeed of the future.
Keywords: climate change-caused flooding; associated diseases; rivers state; Nigeria